Determination of Mayfield's Scalp Clamp Application during Craniotomies; Everything we Should Know - Elkafrawy, Samir A. (New Frontiers in Medicine and Medical Research Vol. 13, 2021)
Using Mayfield's scalp clamp became mandatory in most craniotomies but it leads to potentially hazardous hemodynamic pressor effects. Many interventions like infiltration of local anaesthetics at insertion sites or injecting ketamine, dexmedetomidine, clonidine and magnesium sulphate (MgSO4) had been studied to attenuate these effects. This chapter aims to highlight the efficacy of these interventions through the previously published researches. In conclusion: these undesired pressor effects can be attenuated or even abolished using either one modality or combination of two or more.